2017
DOI: 10.4236/jbm.2017.55004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gaseous Drinks in Wistar Rats Esophagus

Abstract: The consumption of beverages and processed foods, mainly soft drinks, has been incorporated into the usual diet of children, adolescents and adults frequently in recent years. The present study aimed to study the effects of carbonated drinks on Wistar rats, based on the macroscopic and histological morphology of the esophagus. Fifteen Wistar rats were divided into three groups: control group; group fed with ration and cola-type refrigerant ad libitum and group fed with ration and gas industrialized water ad li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Waleska et al determined the effects of fructose present in sufficient amounts in soft drinks and demonstrated that high fructose intake promotes inflammation by accumulation of inflammatory substances such as TNF-alpha 10 . Another concordant study, conducted by Oliveira et al noted histopathological changes in the rats esophagus after exposing them to carbonated water and found inflammatory infiltrate predominantly diffuse mild to moderate and tissue edema in the exposed group 1 .…”
Section: Js Ren Et Al Conducted a Large Prospectivementioning
confidence: 77%
See 2 more Smart Citations
“…Waleska et al determined the effects of fructose present in sufficient amounts in soft drinks and demonstrated that high fructose intake promotes inflammation by accumulation of inflammatory substances such as TNF-alpha 10 . Another concordant study, conducted by Oliveira et al noted histopathological changes in the rats esophagus after exposing them to carbonated water and found inflammatory infiltrate predominantly diffuse mild to moderate and tissue edema in the exposed group 1 .…”
Section: Js Ren Et Al Conducted a Large Prospectivementioning
confidence: 77%
“…They are made from sugar that has no nutritional value and contributes to an excessive intake of empty calories. In addition, consumption of carbonated drinks may substitute for nutritious foods that support normal human growth and development, such as milk, natural juices, and fruits 1 . Moreover, carbonated drinks contribute to the development of incompetence in the lower esophageal sphincter, a delay in gastric emptying, and abnormalities in the esophageal mucosa, all of which increase the risk of developing reflux of gastric contents into the esophagus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation